Pengaruh Financial Distress, Laba Operasi dan Ukuran Perusahaan Terhadap Audit Delay - Cut Sarah Faradista; Hari Stiawan (Universitas Nusantara PGRI Kediri, 2022)
This study aims to prove empirically the effect of financial distress, operating profit and firm size on audit delay. Variable X1 is Financial Distress which is measured using leverage proxy with Debt to Equity Ratio (DER), variable X2 is Operating Profit which is measured using a profit margin ratio measuring instrument by looking at the comparison of net income with sales in a certain period and variable X3 is company size as measured by Ln total assets. While the variable Y is the audit delay which is measured from the closing date of the financial year to the date of issuance of the audit report, to determine the length / span of time for the completion of the audit. This study is a quantitative study using secondary data obtained from the Indonesia Stock Exchange (IDX) for manufacturing the consumer goods sector for the 2016 – 2020 period. The sampling technique used the purposive sampling method with a sample of 20 companies with a total data of 100. From the results of this analysis, it shows that financial distress have no effect on audit delay, operating profit has a significant effect on audit delay and company size have no effect on audit delay. Simultaneously, financial distress, operating profit and firm size have a significant effect on audit delay.